Stability of the Virome in Lab- and Field-Collected Aedes albopictus Mosquitoes across Different Developmental Stages and Possible Core Viruses in the Publicly Available Virome Data of Aedes Mosquitoes - Chenyan Shi (American Society for Microbiology, 2020)
ABSTRACT Aedes mosquitoes can efficiently transmit many pathogenic arboviruses, placing a great burden on public health worldwide. In addition, they also carry a number of insect-specific viruses (ISVs), and it was recently suggested that some of these ISVs might form a stable species-specific “core virome” in mosquito populations. However, little is known about such a core virome in laboratory colonies and if it is present across different developmental stages. In this study, we compared the viromes in eggs, larvae, pupae, and adults of Aedes albopictus mosquitoes collected from a lab colony and compared each to the virome of different developmental stages collected in the field. The virome in lab-derived A. albopictus was very stable across all stages, consistent with a vertical transmission route of these viruses, and formed a possible “vertically transmitted core virome.” The different stages of field-collected A. albopictus mosquitoes also contained this stable vertically transmitted core virome, as well as another set of viruses (e.g., viruses distantly related to Guadeloupe mosquito virus, Hubei virga-like virus 2, and Sarawak virus) shared by mosquitoes across different stages, which might represent an “environment-derived core virome.” To further study this core set of ISVs, we screened 48 publicly available SRA viral metagenomic data sets of mosquitoes belonging to the genus Aedes, showing that some of the identified ISVs were identified in the majority of SRAs and providing further evidence supporting the core-virome concept. IMPORTANCE Our study revealed that the virome was very stable across all developmental stages of both lab-derived and field-collected Aedes albopictus. The data representing the core virome in lab A. albopictus proved the vertical transmission route of these viruses, forming a “vertically transmitted core virome.” Field mosquitoes also contained this stable vertically transmitted core virome as well as additional viruses, which probably represented “environment-derived core virome” and which therefore were less stable over time and geography. By further screening publicly available SRA viral metagenomic data sets from mosquitoes belonging to the genus Aedes, some of the identified core ISVs were shown to be present in the majority of SRAs, such as Phasi Charoen-like phasivirus and Guadeloupe mosquito virus. How these core ISVs influence the biology of the mosquito host and arbovirus infection and evolution deserves to be further explored.